Answer: Choice B
Replace y with x-1 in the first equation.
Solve for x to get x = 5, which leads to y = 4.
========================================================
Step-by-step explanation:
Since y = x-1, we can replace every copy of y with x-1 and solve for x.
This is the substitution step. Think of it like a substitute teacher replacing your regular teacher on a temporary basis.
-5x + y = -21
-5x + (x-1) = -21
-4x -1 = -21
-4x = -21+1
-4x = -20
x = -20/(-4)
x = 5 is the first part of the solution
Then this leads to:
y = x-1
y = 5-1
y = 4 as the second part of the solution
Overall the solution as an ordered pair is (x,y) = (5, 4).
---------------
If you wanted, you could plug x = 5 into the first equation and solve for y like so:
-5x+y = -21
-5(5)+y = -21
-25+y = -21
y = -21+25
y = 4
But it's preferable to use y = x-1 since it's more direct.